AB0085 MODULATION OF CIRCULATING SKELETAL STAMINAL CELLS IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH TOFACITINIB. (2nd June 2020) - Barbati, C.; Spinelli, F. R.; Garufi, C.; Duca, I.; Ceccarelli, F.; Colasanti, T.; Vomero, M.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Rheumatoid arthritis (AR) is an autoimmune systemic inflammatory disease characterized by chronic synovial inflammation resulting in bone damage and erosions, with consequently functional disability. Currently, attempts for regenerative therapies for osteo-cartilage pathologies have proved unsuccessful. Recently, a "pool" of skeletal stem cells ( hSSCs : human skeletal stem cells) able to generating bone cells, has been identified in human bone (1). Objectives: In light of these observations, we aim at characterizing skeletal stem cells in peripheral blood from RA patients candidate to Tofacitinib treatment. Methods: In this pilot study 4 RA patients [4F; mean age 65 years; mean disease duration 19 years] candidate to Tofacitinib treatment and 4 healthy donors (HD), matched by gender and age, were enrolled. Blood samples were collected from each subject of the study, at baseline (T0) and for RA patients, after 1 month of Tofacitinib (T1), to evaluating hSSC (CD45-, CD146-, CD73+, PDPN+, CD164+) by flow cytometry. For this purpose, we performed on whole blood a negative magnetic selection for CD45 cells. Then, the eluate was labeled with antibodies anti CD146-PE, anti CD73-APC, anti CD164 - FITC and anti-Podoplanin (PDPN) PerCP/Cyanine5.5. The acquisition was performed using a FACS Calibur, which included 100, 000 events per sample (Figure 1 ). Results: The hSSCs percentage was significantly lower in RA patients than in HD (p = 0.0286). At T1, after treatment with Tofacitinib, mean hSSCs percentage significantly increased from 1.8% to 4.2 % (p = 0.016 vs RA T0) (Figure 2A ). Correlation analysis showed a significant indirect relation between the percentage of hSSC and disease activity measured by DAS28ESR, SDAI and CDAI (Figure 2B ). Conclusion: The results of this study demonstrate, for the first time, circulating skeletal stem cells and their reduced expression in active RA patients. Tofacitinib treatment leads to a significant increase in hSSCs percentage. This evidence opens up new perspectives on bone repair mechanisms and on deepening of current therapeutic strategies. References: [1]Chan CKF, Gulati GS, Sinha R, Tompkins JV, Lopez M, Carter AC, Ransom RC, Reinisch A, Wearda T, Murphy M, Brewer RE, Koepke LS, Marecic O, Manjunath A, Seo EY, Leavitt T, Lu WJ, Nguyen A, Conley SD, Salhotra A, Ambrosi TH, Borrelli MR, Siebel T, Chan K, Schallmoser K, Seita J, Sahoo D, Goodnough H, Bishop J, Gardner M, Majeti R, Wan DC, Goodman S, Weissman IL, Chang HY, Longaker MT. Identification of the Human Skeletal Stem Cell. Cell. 2018 Sep 20;175(1):43-56.e21. doi: 10.1016/j.cell.2018.07.029. Acknowledgments: none Disclosure of Interests: cristiana barbati: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, cristina garufi: None declared, Ilaria Duca: None declared, fulvia ceccarelli: None declared, Tania Colasanti: None declared, Marta Vomero: None declared, cristiano alessandri Grant/research support from: Pfizer, Guido Valesini: None declared, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi